Therapeutic Strategies Targeting Cancer Stem Cells and Their Microenvironment - Sun, Hao-Ran; Wang, Shun; Yan, Shi-Can; Zhang, Yu; Nelson, Peter J.; Jia, Hu-Liang; Qin, Lun-Xiu; Dong, Qiong-Zhu (Frontiers in Oncology, 2019)
Cancer stem cells (CSCs) have been demonstrated in a variety of tumors and are thought to act as a clonogenic core for the genesis of new tumor growth. This small subpopulation of cancer cells has been proposed to help drive tumorigenesis, metastasis, recurrence and conventional therapy resistance. CSCs show self-renewal and flexible clonogenic properties, that reflect specific tumor microenvironments (TME). The interaction between CSCs and TME is thought to act as a dynamic support system that fosters the generation and maintenance of CSCs. Investigation of the interaction between CSCs and the TME is shedding light on the biologic mechanisms underlying the process of tumor malignancy, metastasis, and therapy resistance. We summarize recent advances in CSC biology and their environment, and discuss the challenges and future strategies for targeting this biology as a new therapeutic approach.